Estudo Experimental de Pavimentos de Concreto: Influência da Posição da Barra de Transferência e do Tipo de Concreto - SILVA, Juliano Rodrigues da (2009)
This work presents an experimental study of the behavior of transverse joints in unreinforced concrete slabs under elastic support. Due to the tensions caused by loads and volumetric variations in the slab, transverse joints when badly executed can cause a efficiency reduction in the shear transfer, thus reducing the useful life of the concrete pavement. To have a better efficiency in the shear transfer in joints of concrete pavements, 500 mm transfer bars are used with bar diameters varying from 10 mm to 32 mm. These bars are positioned at midheight of the sawed joints spaced at every 300 mm. This research seeks to verify the influence of the positioning of the transfer bars and the influence of different types of concrete on sawed joints of concrete pavements. Three different types of unreinforced concrete were used: conventional concrete, steel fiber concrete and self-compacting concrete. The experimental program consisted of the application of static monotonic loading in nine concrete plates, simulating concrete pavements, with dimensions 2200 mm x 600 mm, with a sawed joint at midlength supported by an elastic rubber layer. The experimental results showed that joints with transfer bars performed much better than those joints without transfer bars and that bars located at midheight perform better than those bars positioned at 45 mm from the base. The concrete types were quite different, however the steel fiber concrete was shown to be more efficient than the other two concrete types, and the conventional concrete was more efficient than self-compacting concrete, probably because aggregate interlock is better in conventional concrete